1982
DOI: 10.1002/prep.19820070107
|View full text |Cite
|
Sign up to set email alerts
|

Etude des conditions d'initiation de la pentrite (PETN) par spectrométrie raman ultra‐rapide

Abstract: Untersuchung der Bedingungen fur die Detonationsauslosung bei Pentaerythrittetranitrat (PETN) mittels Ultrakurz-Ramanspektrometrie Die Ultrakurz-Ramanspektrometrie ermoglicht die Untersuchung sehr kurzzeitiger Vorgange, die der Detonation bei Sekundarsprengstoffen vorausgehen. Im Einklang mit friiheren theoretischen Untersuchungen beginnt die Zersetzung dieser Sprengstoffe unter StoBbelastung an der R-NOz Bindung. Wir konnten zwei SchluBfolgerungen aus dieser theoretischen Studie experimentell bestatigen: unte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…These data are unable to differentiate if CO 2 is being generated from chemical reactions in our experiment or if absorptions change based on ambient concentration changes in the long path length of air the MIR traverses. The pressure shifted behavior in this experiment is small compared to static high pressure experiments where pressure shifts were measured to be 2 cm –1 /GPa for the ν s -NO 2 and 0.9–3.18 cm –1 /GPa for ν a -NO 2 ; , however, this phenomenon is commonly observed with the increased temperature in a dynamic experiment. ,,, Similar comparisons of shocked spectra are shown in Figure for the high frequency region.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…These data are unable to differentiate if CO 2 is being generated from chemical reactions in our experiment or if absorptions change based on ambient concentration changes in the long path length of air the MIR traverses. The pressure shifted behavior in this experiment is small compared to static high pressure experiments where pressure shifts were measured to be 2 cm –1 /GPa for the ν s -NO 2 and 0.9–3.18 cm –1 /GPa for ν a -NO 2 ; , however, this phenomenon is commonly observed with the increased temperature in a dynamic experiment. ,,, Similar comparisons of shocked spectra are shown in Figure for the high frequency region.…”
Section: Resultssupporting
confidence: 55%
“…Focusing specifically on chemistry measurements, the results from Ng et al are of particular interest: they suggest NO 2 elimination is dominant at slow heating rates, NO 3 elimination is dominant at fast heating rates, and C–C bond cleavage is dominant during high energy fracture mechanisms similar to explosively driven impactors or gas guns . A similar result was found by Tailleur et al through nanosecond Raman spectroscopy . Results from Dreger et al and Grudzkov et al suggested NO 3 – elimination and subsequent NO 2 + formation as important intermediate reactions in gas gun ring up shock experiments. ,,, Modeling suggests similar chemical paths to the experimental list above: NO 2 scission, ,, NO 3 scission, ,, NO formation, HONO elimination, H-ion formation, O-radical formation, C–C bond cleavage, or CH 2 ONO 2 formation .…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations